Elevated Circulating Adipocyte-Fatty Acid Binding Protein Levels Predict Incident Ischemic Cardiovascular Events in a Longitudinal and Prospective AMI Aging Study - Zhao X; Zhao H; Chen R; Zhou J; Li N; Li J; Yan S; Liu C; Zhou P; Chen Y; Song L; Yan H (Journal of Inflammation Research)
Xiaoxiao Zhao,1 Hanjun Zhao,1 Runzhen Chen,1 Jinying Zhou,1 Nan Li,1 Jiannan Li,1 Shaodi Yan,2 Chen Liu,1 Peng Zhou,1 Yi Chen,1 Li Song,1 Hongbing Yan2 1Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Peking Union Medical College & Chinese Academy of Medical Sciences, BeiJing, People’s Republic of China; 2Department of Cardiology, Fuwai Hospital Chinese Academy of Medical Sciences, ShenZhen, People’s Republic of ChinaCorrespondence: Hongbing Yan, Department of Cardiology, Fuwai Hospital Chinese Academy of Medical Sciences, ShenZhen, 12 Langshan Road, Shenzhen, 518000, People’s Republic of China, Tel +86-13701339287, Email hbyanfuwai2018@163.com Hanjun Zhao, Department of Cardiology, Fuwai Hospital, Chinese Academy of Medical Sciences, No. 167, Beijing, 100037, People’s Republic of China, Tel +86-15210020808, Email 15210020808@163.comBackground: The protein known as Fatty Acid-Binding Protein 4 (FABP4), predominantly found in adipocytes, macrophages, and endothelial cells, has emerged as a pivotal biomarker linking inflammation and metabolism in the context of cardiovascular diseases.Aim: The present investigation sought to elucidate the influence of FABP4 on the prognostic ramifications for patients experiencing ischemic vascular events, which encompass ischemic cerebrovascular occurrences, myocardial infarctions, and cardiovascular mortality.Methods: A total of 1102 consecutive patients diagnosed with acute myocardial infarction (AMI) and aged over 55 years were prospectively enrolled from March 2017 to January 2020. Initially, participants were stratified into three groups according to the tertile levels of FABP4, followed by further categorization based on various lipid profiles and specific inflammatory markers.Results: On follow-up (median 751 days, maximum 1506 days), a total of 158 ischemic events were recorded. 1) In multivariable models meticulously adjusted for age, gender, traditional coronary heart disease factors, Killip classification, and discharge medications, the association of elevated levels of FABP4 (Tertile 3 HR 1.618 [1.061 to 2.468], p=0.026), augmented concentrations of PTX3 (Tertile 3 HR 1.811 [1.211 to 2.710], p=0.004), or LL-37 (Tertile 3 HR 0.651 [0.433 to 0.981], p=0.040) with ischemic risk was markedly intensified. 2) Multivariate HRs associated with 1 standard deviation (SD) (mg/dL) increase in the FABP4 parameters were as follows in different subgroups. 1-SD difference in FABP4 was associated with a 23%, 23%, 21 and 29% increase in ischemic events over after fully adjusted the confounding risk factors among male, patients with hyperlipidemia, hypertension and diabetes respectively. 3) The Kaplan-Meier curve demonstrated significant differences between the tertiles of FABP4 index levels among all enrolled participants (p=0.0180).Conclusion: This study reinforces the utility of FABP4 for enhancing risk stratification specifically among older patients diagnosed with ST-elevation myocardial infarction.Keywords: FABP4, lipid profile, PTX3, LL-37, ischemic vascular events